Incidence and Outcomes of Aortic Dissection in Tabriz, Iran; a Longitudinal Study of 150 Cases - Faridaalaee, Gholamreza; Fathi, Nima; Shahsavarinia, Kavous; Zarei, Hamed; Yousefifard, Mahmoud (Archives of Academic Emergency Medicine, 2024)
Introduction: A comprehensive analysis of the epidemiological features of aortic dissections in Azerbaijan Province, Iran, and their influence on patient survival remains unexplored. This study aimed to determine the incidence of aortic dissection and identify the associated factors of mortality in these patients. Methods: A retrospective longitudinal study was conducted using hospital records of patients diagnosed with aortic dissection in Tabriz, Iran, between 2017 and 2021. The 3-month mortality was followed up via telephone calls using the contact numbers provided in the patients’ records. Then, independently associated factors of mortality were identified using a multivariate stepwise logistic regression analysis. Results: Among the 150 cases of aortic dissection identified, 74% (n = 111) were classified as type A, and 26% (n = 39) were classified as type B. The overall incidence proportion of aortic dissections was 2.35 per 100000 population. In type A dissections, 64% (71 out of 111) of patients received surgical treatment, while 21.6% (24 out of 111) received medical treatment. Among type B dissections, only 23.1% (9 out of 39) underwent surgery. The all-cause mortality rate at 3 months was 52.5% (73 out of 139 patients with complete follow-up), 47 male (54%) and 26 female (50%). Multivariate analysis showed that higher age was independently associated with increased mortality (odds ratio [OR] = 1.03; 95% confidence interval [CI]: 1.00-1.06, p = 0.027). In contrast, patients with DeBakey Type III classification (OR = 0.29; 95% CI: 0.01-0.87, p = 0.027), hypothyroidism (OR = 0.12; 95% CI: 0.01-0.99, p = 0.049), and those who received either surgical treatment (OR = 0.19; 95% CI: 0.05-0.76, p = 0.019) or medical treatment (OR = 0.18; 95% CI: 0.04-0.80, p = 0.024) had a lower chance of mortality. Gender was not found to be associated with the outcome. Conclusion: The study revealed an annual incidence rate of aortic dissection as 2.35 per 100000 population. Aortic dissection, regardless of type, remains a highly fatal condition, with over half of patients dying within 3 months of the initial event. To reduce the high mortality rates associated with aortic dissections, it is crucial to implement specific measures for the early identification of patients and ensure prompt and appropriate care.